SISTEM INFORMASI PURCHSING ORDER (PO) ASET BERBASIS WEB STUDI KASUS FAKULTAS TEKNIK UNIVERSITAS IBNU SINA - Ririt Dwiputri Permatasari; Indah Kusuma Dewi; Agus Suryadi; Tommy Saputra (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2022)
The purpose of this research is to design a purchasing order application at the Faculty of Engineering, Ibnu Sina University, where the current asset inventory submission system is still using the form submitted by the Deputy Dean II. As for the problem in the research where the current inventory submission system is used, there are weaknesses due to the slow submission process from personnel who submit to the leadership and related sections which can only be done in combination, namely by going to the relevant leadership to get approval for the submitted form. The method used in software design is using Rapid Application Development (RAD) and modeling using Unifield Modeling Language (UML). The results of this study indicate that the Purchasing Order Information System (SIPO) can be implemented at the Faculty of Engineering, Ibnu Sina University without serious problems, especially the admin section, that the decision support system is in accordance with the design made and can assist in determining asset requirements at the faculty. Technique. It is recommended to develop using other models such as the Obit Framework and Togaf so that the business process flow can be clearly seen and measured by the needs of the OD and it is also necessary to increase human resources in operating the system. The output of this research is a Web-based SIPO application.